'Each one teach one' visualising black intellectual life in Handsworth beyond the epistemology of 'white sociology'. Issue 1 (2nd January 2020) - Palmer, Lisa Amanda
ABSTRACT: Handsworth, a suburb in north-west Birmingham, became an important generative epistemic location that produced a number of contested discourses on race and racism in Britain during the 1970s and early 1980s. Using archival sources, this article will focus on Handsworth as an important epistemic space where white sociological studies on 'race relations' converged and diverged with the counter-hegemonic political activism of the African Caribbean Self-Help Organisation (ACSHO). This group of young Black working class Pan-Africanists in Handsworth were the coordinating committee for a national delegation of activists who attended the Sixth Pan African Congress in Dar es Salaam, Tanzania in 1974. Their activism in Handsworth was further captured by the photographer, Vanley Burke. The photography of Burke and his archive not only engages with the politics of creating alternative sites of knowledge production, they also enable us to map, trace and reconstruct some of these important sites of Black intellectual life in Britain.